Effects of Dizocilpine, Midazolam and Their Co-Application on the Trimethyltin (TMT)-Induced Rat Model of Cognitive Deficit - Chvojkova, Marketa; Kubova, Hana; Vales, Karel (Brain sciences, 2021)
Research of treatment options addressing the cognitive deficit associated with neurodegenerative disorders is of particular importance. Application of trimethyltin (TMT) to rats represents a promising model replicating multiple relevant features of such disorders. N-methyl-D-aspartate (NMDA) receptor antagonists and gamma-aminobutyric acid type A (GABAA) receptor potentiators have been reported to alleviate the TMT-induced cognitive deficit. These compounds may provide synergistic interactions in other models. The aim of this study was to investigate, whether co-application of NMDA receptor antagonist dizocilpine (MK-801) and GABAA receptor potentiator midazolam would be associated with an improved effect on the TMT-induced model of cognitive deficit. Wistar rats injected with TMT were repeatedly (12 days) treated with MK-801, midazolam, or both. Subsequently, cognitive performance was assessed. Finally, after a 17-day drug-free period, hippocampal neurodegeneration (neuronal density in CA2/3 subfield in the dorsal hippocampus, dentate gyrus morphometry) were analyzed. All three protective treatments induced similar degree of therapeutic effect in Morris water maze. The results of histological analyses were suggestive of minor protective effect of the combined treatment (MK-801 and midazolam), while these compounds alone were largely ineffective at this time point. Therefore, in terms of mitigation of cognitive deficit, the combined treatment was not associated with improved effect.
Keywords: hippocampus; GABA A receptor; trimethyltin; Alzheimer’s disease; cognitive function; neurodegeneration; neuroprotection; dementia; combination therapy; NMDA receptor